2003
DOI: 10.1007/s00775-003-0479-y
|View full text |Cite
|
Sign up to set email alerts
|

A further investigation of the cytochrome b 5–cytochrome c complex

Abstract: The interaction of reduced rabbit cytochrome b 5 with reduced yeast iso-1 cytochrome c has been studied through the analysis of 1 H-15 N HSQC spectra, of 15 N longitudinal (R 1 ) and transverse (R 2 ) relaxation rates, and of the solvent exchange rates of protein backbone amides. For the first time, the adduct has been investigated also from the cytochrome c side. The analysis of the NMR data was integrated with docking calculations. The result is that cytochrome b 5 has two negative patches capable of interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 69 publications
(143 reference statements)
3
22
1
Order By: Relevance
“…Somewhat different results were obtained for the complex of reduced rabbit Cb 5 with reduced yeast Cc (Banci et al, 2003). The chemical-shift perturbations are of similar size and also rather extensive, but cover a somewhat different surface area.…”
Section: Complexes Of Cytochrome B 5 With Cytochrome C and Myoglobinmentioning
confidence: 74%
See 1 more Smart Citation
“…Somewhat different results were obtained for the complex of reduced rabbit Cb 5 with reduced yeast Cc (Banci et al, 2003). The chemical-shift perturbations are of similar size and also rather extensive, but cover a somewhat different surface area.…”
Section: Complexes Of Cytochrome B 5 With Cytochrome C and Myoglobinmentioning
confidence: 74%
“…It is outside the scope of this review to discuss all the earlier work (see Banci et al, 2003;Shao et al, 2003 for an overview). We will focus on the recent two-dimensional NMR spectroscopy studies that have enabled a detailed mapping of the binding sites on both Cb 5 and Cc.…”
Section: Complexes Of Cytochrome B 5 With Cytochrome C and Myoglobinmentioning
confidence: 98%
“…It is to be noted that the interprotein interfaces of cyt b 5 in the Northrup and Salemme model are very similar. A chemical shift mapping study is also available on the interaction between 15 N-enriched reduced yeast iso-1-cyt c and ferrous rabbit cyt b 5 (52). The interprotein interface is close to, but different from, those experiencing the largest shifts in this work, presumably indicating a slightly different interface.…”
Section: Confirmation Of the Resonance Assignments For Horse Cyt Cmentioning
confidence: 82%
“…However, recent NMR studies revealed pronounced dynamics within the complex, suggesting the presence of multiple binding geometries [17], [56]. Depending on the source of Cb 5 and the experimental conditions, formation of binary Cb 5 -Cc and ternary Cb 5 -(Cc) 2 complexes has been reported [54][58].…”
Section: Resultsmentioning
confidence: 99%